ОСОБИСТІСТЬ СТУДЕНТА ЯК СУБ’ЄКТ САМОСТІЙНОЇ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ В УМОВАХ ВИЩОГО ПЕДАГОГІЧНОГО НАВЧАЛЬНОГО ЗАКЛАДУ (Педагогіка вищої та середньої школи, 2022)
The article deals with a personality of the student as the subject of self directed learning activities under conditions of a higher teacher training institution.